2018
DOI: 10.3389/fpls.2018.01652
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Starch Binding Domains and Surface Binding Sites in Enzymes Involved in Starch Biosynthesis

Abstract: Biosynthesis of starch is catalyzed by a cascade of enzymes. The activity of a large number of these enzymes depends on interaction with polymeric substrates via carbohydrate binding sites, which are situated outside of the catalytic site and its immediate surroundings including the substrate-binding crevice. Such secondary binding sites can belong to distinct starch binding domains (SBDs), classified as carbohydrate binding modules (CBMs), or be surface binding sites (SBSs) exposed on the surface of catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…The binding site is at a distance of approximately 25 Å from the active site. Recently, it has been reported that a large number of enzymes catalysing starch degradation or biosynthesis possess surface binding sites (SBSs), which are involved in carbohydrate interaction and are located on the protein surface at a distance from the active site (Møller & Svensson, 2016;Wilkens et al, 2018). The SBSs in some enzymes are proposed to play roles in the recognition of parts of starch chains and also to transfer chains entering or exiting the active site.…”
Section: Substrate Recognition In Ef-amy Imentioning
confidence: 99%
“…The binding site is at a distance of approximately 25 Å from the active site. Recently, it has been reported that a large number of enzymes catalysing starch degradation or biosynthesis possess surface binding sites (SBSs), which are involved in carbohydrate interaction and are located on the protein surface at a distance from the active site (Møller & Svensson, 2016;Wilkens et al, 2018). The SBSs in some enzymes are proposed to play roles in the recognition of parts of starch chains and also to transfer chains entering or exiting the active site.…”
Section: Substrate Recognition In Ef-amy Imentioning
confidence: 99%
“…citreum NRRL B-1299 (17)(18)(19). Surprisingly, additional surface (or secondary) binding sites more distant from the active site were never described in the domains A, B or IV of GH70 dextransucrases contrary to what was observed for GH13 enzymes, which belong to the same clan as the GH70 enzymes and for which the distant surface binding sites were found to play a role in substrate targeting, allosteric regulation and also processivity (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of this sugar nucleotide takes place from glucose-1-phosphate (Glc1P) and ATP in a reaction catalyzed by ADP-Glc pyrophosphorylase (EC 2.7.7.27, ADP-Glc PPase) ( Ballicora et al., 2003 ; Ballicora et al., 2004 ). The metabolic route follows by the action of enzymes implicated in branching, debranching, phosphorylation, and de-phosphorylation of the polymer under formation ( Wilkens et al., 2018 ). Most of these enzymes arise in isoforms exhibiting changes in specificity and ability to interact with different partners forming multi-protein complexes of functional relevance for the production of the polysaccharide ( Crofts et al., 2017 ; Wilkens et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic route follows by the action of enzymes implicated in branching, debranching, phosphorylation, and de-phosphorylation of the polymer under formation ( Wilkens et al., 2018 ). Most of these enzymes arise in isoforms exhibiting changes in specificity and ability to interact with different partners forming multi-protein complexes of functional relevance for the production of the polysaccharide ( Crofts et al., 2017 ; Wilkens et al., 2018 ). The step producing ADP-Glc is rate-limiting in the starch biosynthetic pathway ( Kavakli et al., 2001b ; Ballicora et al., 2003 ; Ballicora et al., 2004 ; Tuncel and Okita, 2013 ).…”
Section: Introductionmentioning
confidence: 99%